The captain and the glory : an entertainment - Eggers, Dave (Alfred A. Knopf, 2019)
"When the decorated Captain of a great ship descends the gangplank for the final time, a new leader, a man with a yellow feather in his hair, vows to step forward. Though he has no experience, no knowledge of nautical navigation or maritime law, and though he has often remarked he doesn't much like boats, he solemnly swears to shake things up. Together with his band of petty thieves and confidence men known as the Upskirt Boys, the Captain thrills his passengers, writing his dreams and notions on the cafeteria wipe-away board, boasting of his exemplary anatomy, devouring cheeseburgers, and tossing overboard anyone who displeases him. Until one day a famous pirate, long feared by passengers of the Glory but revered by the Captain for how phenomenally masculine he looked without a shirt while riding a horse, appears on the horizon... Absurd, hilarious, and all too recognizable, The Captain and the Glory is a wicked farce of contemporary America only Dave Eggers could dream up."--Provided by publisher.